Behavioral Lifestyles and Survival: A Meta-Analysis - Fernández-Ballesteros, Rocío; Valeriano-Lorenzo, Elizabeth; Sánchez-Izquierdo, Macarena; Botella, Juan (Frontiers in Psychology, 2022)
The aim of the study is to determine the association between Behavioral Lifestyles (regular physical activity, healthy diet, sleeping and weight control) and longevity in the elderly. A search strategy was conducted in the PsycInfo, Medline, PubMed, Web of Science (WoS) and Scopus databases. The primary outcome was mortality / survival. Four variables (mean of participant’s age at the baseline of the study, follow-up years of the study, gender, and year of publication) were analyzed to evaluate the role of potential moderators. Ninety-three articles, totaling more than 2,800,000 people, were included in the meta-analysis. We found that the lifestyles analyzed predict greater survival. Specifically, doing regular physical activity, engaging in leisure activities, sleeping 7-8 hours a day, and staying outside the BMI ranges considered as underweight or obesity are habits that each separately has a greater probability associated with survival after a period of several years.